ANALISIS TRANSAKSI JUAL BELI LOGAM MULIA PERSPEKTIF HUKUM EKONOMI SYARIAH (Studi Kasus PT. Pegadaian Syariah CPS Pasar Legi Jombang) - Wulan Sari, Putri Diana; Syai'in; M. Chamim (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2023)
Abstract: This study aims to analyze the sale and purchase of precious metals at PT. Pegadaian Syariah CPS Pasar Legi Jombang and analyze the perspective of sharia economic law on buying and selling precious metals at PT. Sharia Pawnshop CPS Legi Market Jombang. The research method used is qualitative research with data analysis techniques used through inductive and descriptive methods. The data obtained from interviews, documentation, and library data collection. The results of the study indicate that the sale and purchase of precious metals is carried out with a credit system which according to an Islamic perspective, more precisely according to the MUI fatwa No. 77 of 2010 an installment or credit system may be carried out in precious metal transactions. Keywords: Sharia Pawnshop, Precious Metals, Islamic Law.